2016
DOI: 10.3892/br.2016.706
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in hereditary diffuse gastric cancer

Abstract: Abstract. In 2012, gastric cancer (GC) was the third cause of mortality due to cancer in men and women. In Central and South America, high mortality rates have been reported. A total of 95% of tumors developed in the stomach are of epithelial origin; thus, these are denominated adenocarcinomas of the stomach. Diverse classification systems have been established, among which two types of GC based on histological type and growth pattern have been described as follows: Intestinal (IGC) and diffuse (DGC). Approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…MiRNAs have been reported as oncogenes, tumor suppressors, and regulators in numerous cancers, such as gastric cancer and breast cancer [Yang et al, ; Suarez‐Arriaga et al, ]. Similarly, we found that the expression of miR‐892a was up‐regulated in cancer tissues compared with the matched adjacent tissues.…”
Section: Discussionsupporting
confidence: 74%
“…MiRNAs have been reported as oncogenes, tumor suppressors, and regulators in numerous cancers, such as gastric cancer and breast cancer [Yang et al, ; Suarez‐Arriaga et al, ]. Similarly, we found that the expression of miR‐892a was up‐regulated in cancer tissues compared with the matched adjacent tissues.…”
Section: Discussionsupporting
confidence: 74%
“…MiRNAs regulate target gene expression by binding to the 3′ UTR region of the target gene and are involved in the pathogenic processes of various human diseases, including GC [ 27 , 28 ]. The analysis of miRNA and gene expression profiles showed that the let-7 miRNA family plays a central role in the regulation of tumorigenesis [ 29 , 30 ]. And the let-7 family members are the hallmarks of several cancers [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The E-cadherin (CDH1) gene has been identified in approximately 40% of families showing a pedigree consistent with HDGC and about 80% penetrance consistent with an autosomal dominant mode of inheritance [23]. Hereditary diffuse gastric cancer can predispose to lobular breast cancer J Gastrointestin Liver Dis, June 2017 Vol.…”
Section: Geneticsmentioning
confidence: 99%
“…Diffuse gastric cancer families with BRCA2 mutations would likely benefit from preventive and therapeutic measures. In studying an HDGC family negative for the CDH1 mutation, these authors identified three candidate genes, the most promising of which is INSR, which may affect E-cadherin glycosylation [23]. Hansford et al suggested that unexplained cases of HDGC are likely attributable to a combination of mutations in as yet unidentified genes, phenocopies among families, or other abnormalities related to the CDH1 locus or pathway [22].…”
Section: Geneticsmentioning
confidence: 99%